PEMANFATAN CAMPURAN PANGKASAN TUMBUHAN IN SITU DANKOTORAN TERNAK ULAT JERMAN UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN JAGUNG - Riyanto Djoko; Presti Ameliawaty (Universitas Tribhuwana Tunggadewi, 2017)
Field trial designed by a randomized block design factorial, three replication. The first factor is plant prunings 3 kinds of material mixed with cattle dung manure worms Germany and the second factor treatment fertilizer composition comprising a mixture of three kinds consists of: Tithoniadiversifolia, Cromolaenaodorata and Gliricidiasepium. Fertilizer composition comprising a mixture of: 90% of plants + 10% manure, 80% growth + 20% manure and 70% growth + 30% manure. Of the two factors obtained 9 treatment combinations. The observationdone for variable of : root dry weight, stem dry weight, dry weight of cob and dry seed weight per ear at harvest. Statistical analysis of the parameters of the observations were made using a variety of tests (test F) Random Block Factorial and continued with Duncan test level of 5%. Results of the experiments showed that: a). The use of a mixture of crop plants in situ with caterpillar droppings German influence on stem dry weight, root dry weight, dry weight and the weight of dry seed cob corn crop. b). The highest weight of dry seed treatment derived from the addition of a mixture of crop Gliricidia sp. 70% with caterpillar droppings Germany 30% (165 grams), while the lowest of the crop mix treatment Titonia sp. 90% with caterpillar droppings Germany 10% (112.3 g).